The Impact of Utilizing Big Book-Based Learning Media on Student’s Learning Interest and Conceptual Understanding of Acid-Base Chemistry Topics - Rusdyana, Yuyun; Muhajir; Hanifah, Sri Yuni (LPPM STKIP Kusuma Negara, 2025)
This study explores the use of big book-based learning media and its impact on students’ interest in learning and understanding of acid-base concepts in 11th-grade chemistry at SMAN 1 Ketapang. The research applies a quantitative approach with a quasi-experimental design. Observations revealed that students’ learning interest and conceptual understanding of acid-base topics were still low. To measure the effect, an independent sample t-test was conducted. The results show a significance value of 0.000 < 0.05 for both learning interest and conceptual understanding, indicating a significant improvement after using big book-based media. The findings demonstrate that big books not only effectively enhance students’ motivation and comprehension but also make learning more engaging through visually appealing and well-structured content. This format allows students to read and understand material more easily, which stimulates interest and supports deeper understanding. Consequently, big book-based media can serve as an alternative solution for teachers aiming to improve students’ engagement and conceptual mastery, particularly in challenging topics like acid-base chemistry. The study emphasizes the importance of integrating creative and visually rich learning materials to foster active learning and improve educational outcomes in science subjects.